2012
DOI: 10.3109/2000656x.2012.669184
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hypertrophic scars: Evolution and susceptibility

Abstract: Formation of hypertrophic scars is a common complication of wound healing, and at present little is known about the incidence and risk factors. Our aim was to analyse the incidence, progression, and regression of postoperative hypertrophic scars over time and to identify risk factors of hypertrophic scars. Patients who had had bilateral reduction mammoplasty or median sternotomy incision were included in the study. All patients were examined at 3 and 12 months postoperatively. We recorded: height, weight, alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The phenotypic differences were stable over time in culture, suggesting that they are an inherent property of the cells. Furthermore, the key differences did not depend on whether skin cells originated from breast or abdominal skin, both prone to scar formation [23], [24], suggesting that the differences to GFBLs are a general characteristic of SFBLs. Whether this phenotypic difference depends on embryonic origin of the cells remains to be shown, as gingival cells mostly originate from the neural crest while abdominal and breast SFBLs are of mesodermal origin [11], [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The phenotypic differences were stable over time in culture, suggesting that they are an inherent property of the cells. Furthermore, the key differences did not depend on whether skin cells originated from breast or abdominal skin, both prone to scar formation [23], [24], suggesting that the differences to GFBLs are a general characteristic of SFBLs. Whether this phenotypic difference depends on embryonic origin of the cells remains to be shown, as gingival cells mostly originate from the neural crest while abdominal and breast SFBLs are of mesodermal origin [11], [17].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, they retain stem or tumor stromal cell phenotype better than traditional 2D cultures [21], [22]. Therefore, in the present study, the 3D culture model was used to compare the phenotype of human oral mucosal fibroblasts from attached gingiva, tissue characterized by little scar formation, with fibroblasts from human breast and abdominal skin, two areas of skin prone to excessive scar formation [23], [24]. The findings showed that gingival fibroblasts proliferated faster and expressed significantly higher levels of molecules that are involved in modulation of inflammation and ECM remodeling (MMPs), while skin cells showed significantly elevated expression of TGF-β signaling, ECM, myofibroblast and cell contractility-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies consist of retrospective case note reviews where any documentation of a scar which is red or raised constitutes a diagnosis of HTS [5, 9]. Other studies use the height of the scar alone [10, 11] or VSS [12] to diagnose HTS. In addition, some papers consider hypertrophic scars alone whereas others combine HTS with contracted or keloid scars to give an overview of pathological scarring [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is difficulty comparing results between existing studies due to different denominators and sample sizes, heterogeneous patient populations, a lack of consistent definitions of risk factors and a lack of consistent and valid scar outcome classification [8]. Despite the high prevalence of hypertrophic scarring as a complication of burn injury, few prospective studies have been conducted to systematically identify factors associated with their occurrence in children [9], and hypertrophic scars and keloids are not always well-differentiated [10]. …”
Section: Introductionmentioning
confidence: 99%